Effect of phosphate and sulphate loading rate on the selection of PHA accumulating phototrophic mixed cultures - Pereira, Bruno Alexandre das Neves (2018)
Petroleum-based plastics have massively contributed to a substantial increase in environmental pollution. Biobased plastics have emerged as a much-needed alternative solution to fossil dependent synthetic polymers. Polyhydroxyalkanoates (PHA) are a promising group of biobased and biodegradable displaying similar features to conventional plastics. Their high-cost production has become a hindrance to its economical applicability. Alternative low-cost processes of production can be achieved by using renewable raw materials (as feedstock) combined with the use of mixed microbial cultures (MMCs). Extensive research aiming the decrease of PHA production costs focused on the use of phototropic mixed cultures (PMC) enriched in purple bacteria is being developed (Fradinho et al. (2014)). The culture is selected under a feast and famine regime (FF) being able to reach up to 30% PHA / VSS using acetate as a carbon source in light/dark cycles. The permanent feast regime occurs as an alternative to the well-studied FF strategy and consists of a constant presence of carbon and the absence of electron acceptors. Ultimately, microorganisms such as purple bacteria will dissipate the reducing power (generated by the consumption of carbon source) and PHA will be formed. Using this strategy, Fradinho et al. (2016) obtained a 60% PHA/VSS content in a test with high light intensity. This work comes in the continuity of a previous study integrating a European project, NoAW, that aims for the valorisation of agro-industrial residues and for the production of valuable biobased products while exploring the phototrophic capacity of PMC under a permanent feast regime. PMC selection was done in an SBR under 24h cycles (12h of light and 12h dark) operating in a continuous feeding mode during the light phase. The culture was fed synthetic medium composed of a mixture of volatile fatty acids (VFAs) simulating fermented waste of cow manure and maize silage. During the reactor operation, several operating conditions were tested and the most promising results were obtained under the double limitation of phosphorus and sulfur. A decrease in the amount of algae population (phototrophic organisms that do not produce PHA) was observed which contributed to a higher percentage of PHA production. Indeed, the culture attained a PHA content of 31% PHA / VSS (25 Cmmol/L) in accumulation tests with optimized light intensity and acetate as carbon source. This highly attractive photosynthetic cultures’ ability opens new doors in its applicability in wastewater treatment plants (WWTP) that are under the direct illumination of sunlight. Wastewater could become a viable source of carbon for the production of valuable bioproducts, giving a highly desirable contribute to the implementation of a European circular economy.